2021
DOI: 10.46827/ejpe.v7i4.3985
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Psychological Determinants of Leisure Time Physical Activity Among Adolescents in Nigeria

Abstract: <p>Despite the numerous benefits associated with leisure time physical activity (LTPA), it is quite worrisome that the habit of regularly engaging in LTPA is rare among Nigerians, especially among adolescents who are found in myriads of sedentary lifestyle behaviour as a result of technological and economical advancement. The present study examined socio-demographic and psychological determinants of LTPA among adolescents in Nigeria. A cross-sectional study was conducted and multistage sampling technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that fulfilling BPNs increases individuals' impetus to engage in PA with greater commitment and determination, which in turn promotes overall well-being and active lifestyles in various countries , Gholidahaneh et al 2020). While most of the studies on PA in Nigeria have focused on sociodemographic, personal, physical, psychological, and environmental factors that influence and associate with PA among different populations, especially among adolescents (Oluwasanu and Oladepo 2017, Oguntuase et al 2021, Adeniyi et al 2016, Adeniyi et al 2011, Ugwueze et al 2021, there is no evidence of a study on BPNs predicting PA participation among young adults in Nigeria. Therefore, this study investigates basic psychological needs predicting physical activity participation among young adults in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that fulfilling BPNs increases individuals' impetus to engage in PA with greater commitment and determination, which in turn promotes overall well-being and active lifestyles in various countries , Gholidahaneh et al 2020). While most of the studies on PA in Nigeria have focused on sociodemographic, personal, physical, psychological, and environmental factors that influence and associate with PA among different populations, especially among adolescents (Oluwasanu and Oladepo 2017, Oguntuase et al 2021, Adeniyi et al 2016, Adeniyi et al 2011, Ugwueze et al 2021, there is no evidence of a study on BPNs predicting PA participation among young adults in Nigeria. Therefore, this study investigates basic psychological needs predicting physical activity participation among young adults in Nigeria.…”
Section: Introductionmentioning
confidence: 99%